(untitled) (International journal of artificial intelligence, 2026)
This article examines the concept of competition and the role of competitive strategies in modern business environments. In the context of globalization and rapidly evolving markets, organizations are increasingly required to develop effective strategies to sustain competitive advantage and ensure long-term success. The study explores the theoretical foundations of competition, including its types, characteristics, and impact on market dynamics. Particular attention is given to widely recognized strategic frameworks such as Porter’s Generic Strategies, which include cost leadership, differentiation, and focus strategies.